If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(-2)(5X + -8y) = 0 Multiply 7 * -2 -14(5X + -8y) = 0 (5X * -14 + -8y * -14) = 0 (-70X + 112y) = 0 Solving -70X + 112y = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-112y' to each side of the equation. -70X + 112y + -112y = 0 + -112y Combine like terms: 112y + -112y = 0 -70X + 0 = 0 + -112y -70X = 0 + -112y Remove the zero: -70X = -112y Divide each side by '-70'. X = 1.6y Simplifying X = 1.6y
| -10-x=-13 | | 9z+5-7z=59-7z | | 6x+3-1=26 | | 3(x-2)+x=7(2x+1)-3 | | (3x-2.5)-(2x-2.1)= | | 30=-26-8x | | -7h-17-6+4h=17-h | | x^4=8x^6+128x^2-16 | | 5[2x-3]=3[3x+2] | | (3c-8)-(-5c+3)= | | f^2=-44 | | 2+x=-4x+12 | | 3(2x+-5)=2(3x+-1)-13 | | 28=-9(7h+4) | | -6(5-r)=12 | | 15+-2C=7 | | 2a^2-5a=0 | | 2=-4x+5x+6 | | 4x^2=-16x+4 | | 2.3x+2=12.3x+2.8x-6 | | x+15=10-x+10 | | 3A^2-4AB+B^2=0 | | 3(2x+-5)=2(3x+-1)+7 | | 5x-12=4x+20 | | -4.5x-y=3 | | 0=96x-12x^2 | | x+1.4=1.09x | | 1862=49(p+10) | | 10r^2+20=200 | | d-2d+3=3 | | 7x-4=-11-10(6-x) | | 7x^2=8x-1 |